2006
DOI: 10.1523/jneurosci.3528-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Development in the Absence of Programmed Cell Death: Phenotypic Alteration of Motoneurons and Muscle

Abstract: The widespread, massive loss of developing neurons in the central and peripheral nervous system of birds and mammals is generally considered to be an evolutionary adaptation. However, until recently, models for testing both the immediate and long-term consequences of preventing this normal cell loss have not been available. We have taken advantage of several methods for preventing neuronal death in vivo to ask whether rescued neurons [e.g., motoneurons (MNs)] differentiate normally and become functionally inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 74 publications
5
44
0
Order By: Relevance
“…For example, in previous studies, we found that a subset of excess motoneurons rescued from PCD cannot maintain their original phenotype and either become atrophied or differentiate abnormally (Sun et al, 2003;Buss et al, 2006b). In the present study, we found that misplaced PCs also exhibit an atrophied morphology and limited differentiation with eventual loss of a biochemical marker (CB) for PCs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…For example, in previous studies, we found that a subset of excess motoneurons rescued from PCD cannot maintain their original phenotype and either become atrophied or differentiate abnormally (Sun et al, 2003;Buss et al, 2006b). In the present study, we found that misplaced PCs also exhibit an atrophied morphology and limited differentiation with eventual loss of a biochemical marker (CB) for PCs.…”
Section: Discussionsupporting
confidence: 58%
“…The PCD of postmitotic neurons can also occur before synaptogenesis, at which time it may function to eliminate ectopically located neurons and aberrant axon projections (Clarke et al, 1998;Thanos, 1999;Oppenheim et al, 2001). The proapoptotic gene Bax is required for the normal PCD of many populations of developing postmitotic neurons (White et al, 1998;Sun et al, 2003Sun et al, , 2004Buss et al, 2006b), whereas the PCD of proliferating neuronal progenitor cells is less affected by Bax deletion, suggesting that the molecular cell death machinery differs for mitotic versus postmitotic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was also demonstrated that a substantial population of unmyelinated axons was rescued by bax deletion. 34,37 While the ventral roots of adult wild-type mice normally contain very low numbers of unmyelinated axons, this is also true for our lineages of bcl-2-null mice (Supplementary Figure 1). Given the model proposed for bcl-2, and the nature of interactions between Bcl-2 and Bax, this finding is not surprising and paints a consistent picture of Bcl-2's action.…”
Section: Discussionmentioning
confidence: 60%
“…[34][35][36] That gamma motor neurons require glial cell line-derived neurotrophic factor (GDNF) for survival derived from muscle spindles is suggested from studies in which significant losses of small diameter motor axons are observed in gdnf heterozygous animals. Similarly, transgenics ectopically expressing GDNF within skeletal muscle exhibit a substantial increase in small diameter motor axons within the L4 ventral root, 34,35 although the precise nature of the motor neurons contributing these axons is unclear. Analysis of the L4 ventral root in bax null mice reveals a significant increase in total numbers of myelinated axons, which is contributed exclusively by small diameter axons believed to be derived from gamma motor neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation